Le droit à l’image : le Cinéma Novo brésilien et l’apparaître - Gustavo Chataignier (Appareil)
This text aims to present "Brazilian Cinema Novo", the Brazilian expression of what is generally called "new wave cinema" taking place all around the world in the late 1950s. Working within (as well as worked by) its Italian and French influences, respectively neorealism and the Nouvelle Vague, the Cinema Novo combines their recreation gesture with folk and national imaginary elements. Therefore, it emerges few major directors, like for example Glauber Rocha. In this regard, his filmography – mainly Black god, white devil [Deus e o diabo na terra do sol, 1964] – will be read as a "mythological rationality", whose creativeness, by means of proper cinema aesthetic procedures, brings up a new visibility. One believes, finally, that cinema sensible forms are able to establish another possible world.